2009
DOI: 10.1177/0363546509339357
|View full text |Cite
|
Sign up to set email alerts
|

Sports Injuries During the Summer Olympic Games 2008

Abstract: Results: 1055 injuries were reported, resulting in an incidence of 96.1 injuries per 1000 registered athletes. About half of the injuries (49.6%) were expected to prevent the athlete from participating in competition or training. The most prevalent diagnoses were ankle sprains and thigh strains. A quarter of the injuries were incurred during training and 72.5% in competition.One third of the injuries were caused by contact with another athlete, followed by overuse (22%) and non-contact incidences (20%). Injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
443
7
36

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(547 citation statements)
references
References 37 publications
38
443
7
36
Order By: Relevance
“…Our frequency of injuries in taekwondo, equal to 17.2%, is significantly higher (p = 0.032). Compared with other Olympic combat sports, judo time loss injury frequency of 6% -9% during the last two SOGs was clearly lower than in taekwondo (16% -18%) but slightly higher than in boxing (4% -8%) and wrestling (5% -6%), respectively (Junge, Engebretsen, Mountjoy et al, 2009;Engebresten, Soligard, Steffen et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our frequency of injuries in taekwondo, equal to 17.2%, is significantly higher (p = 0.032). Compared with other Olympic combat sports, judo time loss injury frequency of 6% -9% during the last two SOGs was clearly lower than in taekwondo (16% -18%) but slightly higher than in boxing (4% -8%) and wrestling (5% -6%), respectively (Junge, Engebretsen, Mountjoy et al, 2009;Engebresten, Soligard, Steffen et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…Despite those differences, studies have shown that most combat sports can be characterized as high-intensity, intermittent sports (Campos, Bertuzzi, Dourado, et al, 2012;Artioli, Gualano, Franchini et al, 2009;Franchini, Del Vecchio, Matsushigue et al, 2011;Terbizan & Selievold, 1996;Del Vecchio, Hirata, & Franchini, 2011). Consequently, injury risk had been consistently high in these athletes (Kobayashi, Kanamura, Koshida et al, 2010), even if the International Olympic Committee initiated and developed the injury and illness surveillance system during the 2008 Beijing and 2012 London Olympics (Junge, Engebretsen, Mountjoy et al, 2009;Engebresten, Soligard, Steffen et al, 2013). In the literature, a few prospective and retrospective studies as well as case reports dealing with combat injuries are available (Souza, Monteiro, Del Vecchio et al, 2006;Green, Petrou, Fogarty-Hover et al, 2007;Pierantozzi & Muroni, 2009) …”
Section: Introductionmentioning
confidence: 99%
“…The protocol for collecting epidemiological data on the player's injuries was based on the definition and injury registry system coming from Junge et al [31], used in follow-up studies of the International Olympic Committee (IOC) and the International Federation of Football Associations (FIFA). Added to that, a self-reported questionnaire [32] was used to record the number, type, and severity of injuries sustained during the previous sports season (which lasted approximately one year), marking clearly the player's current situation being injured or not injured at the time of the study.…”
Section: Variables and Instrumentsmentioning
confidence: 99%
“…In fact Bruce-low and Smith 14 have noted that, unless your goal is to improve the ability to perform the specific lifts involved with the sport of Olympic weightlifting, there is no need to perform them over and above more traditional resistance training methods. Junge, et al 22 and Engebretsen, et al 23 have reported the prevalence of weightlifting injury in the 2008 Beijing, and 2012 London Summer Olympics. The statistics of 43 injuries from 255 competitors (16.9%: 2008), and 44 injuries from 252 competitors (17.5%: 2012) equate to a 1 in 6 chance of injury, from what we can assume to be the most SKILLED Olympic Weightlifters.…”
Section: Recent Cases Of Serious Injurymentioning
confidence: 99%